2014
DOI: 10.1590/s0080-623420140000300013
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to statin treatment and associated factors in female users from the Unified Health System (SUS)

Abstract: Objective: To identify the adherence rate of a statin treatment and possible related factors in female users from the Unified Health System. Method: Seventy-one women were evaluated (64.2 ± 11.0 years) regarding the socio-economic level, comorbidities, current medications, level of physical activity, self-report of muscular pain, adherence to the medical prescription, body composition and biochemical profile. The data were analyzed as frequencies, Chi-Squared test, and Mann Whitney test (p<0.05). Results: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(40 reference statements)
0
1
0
2
Order By: Relevance
“…The extrapolation of these results to humans seems to suggest that physically active individuals prior to treatment with statins may be protected from the deleterious drug effects, indicating that the prescription of exercise training prior to drug therapy with statins might be a preventive measure to muscle effects. Despite the evidence, Bonfim et al 51 recently found that many patients with dyslipidemia undergoing treatment with statins are sedentary and, therefore, would not be previously protected if they chose to carry out changes in their lifestyle.…”
Section: Resultsmentioning
confidence: 99%
“…The extrapolation of these results to humans seems to suggest that physically active individuals prior to treatment with statins may be protected from the deleterious drug effects, indicating that the prescription of exercise training prior to drug therapy with statins might be a preventive measure to muscle effects. Despite the evidence, Bonfim et al 51 recently found that many patients with dyslipidemia undergoing treatment with statins are sedentary and, therefore, would not be previously protected if they chose to carry out changes in their lifestyle.…”
Section: Resultsmentioning
confidence: 99%
“…Alguns estudos avaliaram a custo-efetividade da utilização de estatinas pelo Sistema Único de Saude (SUS); 2,3 contudo, a aderência ao tratamento foi pouco estudada em grupos seletos (mulheres), atingindo 15,5% em pequena série. 4 Com a recente incorporação ao arsenal terapêutico de novos medicamentos altamente eficazes no controle de hipercolesterolemia, 5,6 ainda que de elevado custo, os hospitais terciários tornaram-se ponto de convergência de pacientes com perfil lipídico muito alterado, visando à sua prescrição pelo sistema público. No entanto, pouco se conhece do perfil lipídico e do tratamento de pacientes em seguimento ambulatorial nessas instituições.…”
Section: Introductionunclassified
“…Na atenção básica, os atendimentos de enfermagem são mais rotineiros que as consultas médicas, fomentando maior relação destes profissionais com os pacientes. Estes fatores cooperam de maneira singular na adesão ao tratamento medicamentoso e na identificação precoce de seus efeitos colaterais, bem como para o aconselhamento dos pacientes (Bonfim et al, 2014).…”
Section: Introductionunclassified